Да гісторыі ўжывання слоў талерантнасць, памяркоўнасць і цярплівасць у беларускай мове. Дыяхранічны аспект - Kozłowska-Doda, Jadwiga (Acta Polono-Ruthenica, 2020)
The Author of the article is taking over the meaning of the words талерантнасць (eng. tolerance), памяркоўнасць (eng. reasonableness), цярплівасць (eng. patience), which are used for the description of the term tolerance in Belarusian language. The Author is looking after its appearance at the Belarusian language dictionaries, analyzing its etymology, comparing synonyms, antonyms and hyperonyms. At the same time the Author specifies the time range of specific changes of the form and content. It is necessary to pay attention to the question concerning to the subject of tolerance from a concrete person whose characteristic features are: the acceptance of other people, kindness, understanding, appreciation and respect towards other people, social groups (especially religious and national), up to the characteristics of abstract conceptions, ideas. On the other hand I should admit the absence at the vocabulary database of the content ‘understanding and respect for the different sexual orientation groups’, which begins to appear just at modern texts at the tern of the XX and the XXI century (so text researches as analyses of the questionnaires which will be carried out among Belarusian youth will be done by the Author in the nearest feature). At the Belarusian language dictionaries nation is minimally characterized by the concept tolerance (refers to the joint subject). At the article the Author has used the methodology of cognitive definition, proposed by Jerzy Bartminski.